French national addictovigilance follow-up of zolpidem between 2014 and 2020: evolution of drug abuse, misuse and dependence before and after the regulatory change. (7th February 2023) - Aquizerate, Aurélie; Laforgue, Edouard-Jules; Istvan, Marion; Rousselet, Morgane; Gerardin, Marie; Jouanjus, Emilie; Libert, Frédéric; ,; Guerlais, Marylène; Victorri-Vigneau, Caroline
Abstract: Background: Since the appearance of zolpidem on the market, the occurrence of serious cases of abuse, misuse and dependence have come to the attention of authorities. In view of the increase in the number and severity of cases among zolpidem users and the predominant presence of zolpidem in falsified prescriptions, the French Health Authorities implemented part of the narcotics regulation for zolpidem in April 2017. The objective of this article was to describe the evolution of the abuse, dependence and misuse of zolpidem. Methods: We used three data sources: (i) zolpidem is a reimbursable and strictly prescription drug in France. Medic'AM is a public database that indicates the number of tablets reimbursed each month in France for each reimbursable drug. This database has been analyzed as a proxy of the exposure of the French population to zolpidem; (ii) all French cases of drug dependence or abuse reported by health professionals (regulatory obligation) and (iii) an epidemiological tool based on the surveillance of falsified prescriptions over two periods: the 3-year period before the regulatory measure (2014–16) and the 3-year period after the regulatory measure (2018–20). Results: This regulatory change had two immediate consequences: a sharp decline in falsified prescriptions and a decrease of ∼57% between the two study periods in the zolpidem reimbursement data. Markers of problematic consumption remained after the regulatory change with worsening cases, particularly for people who were genuinely dependent and/or had comorbidities or misusers for whom zolpidem was the substance of interest, whose proportion increased significantly in the addictovigilance notification system, from 43.6% ( N = 107) to 59.3% ( N = 127) ( P < 0.01). Conclusions: Further monitoring is needed in light of these persistent markers of problematic consumption.